Experimental Study of the Effect of Increased Compression Ratio on the Torque and Power of the Honda CB 150R Engine Using E85 Fuel - Yuli Mafendro Dedet Eka Saputra; Muhammad Hidayat Tullah (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
Switching from fossil fuels to alternative fuels requires adjusting several engine parameters to avoid a decrease in engine torque and power. This happens because of the different properties of different fuels. One of the parameters that must be set is the compression ratio. This study aims to determine the effect of increasing the compression ratio on the torque and power of the Honda CB 150R engine using 85% bioethanol (E85) as fuel. The research method used an experimental method with 2 types of fuel and variations in the compression ratio. From the research results, it can be seen that the torque and power using E85 fuel have increased respectively by 1.08% and 1.5% when compared to the standard compression ratio using fossil fuels. Pergantian bahan bakar dari fosil ke bahan bakar alternatif membutuhkan pengaturan pada beberapa parameter engine untuk menghindari terjadinya penurunan pada torsi dan daya mesin. Hal ini terjadi karena perbedaan dari properties bahan bakar yang berbeda. Salah satu parameter yang harus di atur adalah rasio kompresi. Penelitian ini bertujuan untuk mengatahui pengaruh dari peningkatan rasio kompresi terhadap torsi dan daya engine Honda CB 150R menggunakan bahan bakar bioetanol 85% (E85). Metode penelitian menggunakan metode eksperimen dengan 2 jenis bahan bakar dan variasi pada rasio kompresi. Dari hasil penelitian terlihat bahwa torsi dan daya dengan menggunakan bahan bakar E85 mengalami peningkatan masing-masing sebesar 1,08 % dan 1,5 % jika dibandingkan dengan rasio kompresi standard menggunakan bahan bakar fosil.